2013
DOI: 10.3109/14767058.2013.852172
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of cervical vaginal fluid proteins among women in recurrent preterm labor

Abstract: The lack of confirmation of potential biomarkers identified by mass spectrometry and ELISA demonstrates the challenges of validating PTB biomarkers and suggests that a panel of biomarkers would improve the predictive value of CVF testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…This study revealed specific pro-inflammatory proteomic profiles Various proteins have been linked to intra-amniotic infection in non-human primates or recurrent spontaneous preterm birth in humans, [50][51][52] including several proteins identified in this study.…”
Section: Commentmentioning
confidence: 60%
See 1 more Smart Citation
“…This study revealed specific pro-inflammatory proteomic profiles Various proteins have been linked to intra-amniotic infection in non-human primates or recurrent spontaneous preterm birth in humans, [50][51][52] including several proteins identified in this study.…”
Section: Commentmentioning
confidence: 60%
“…Other previously documented biomarkers of preterm birth were also found to be differentially expressed in cases of CI including increased cysteine-rich secretory protein 3 levels, a protein released upon neutrophil degranulation, 51 and decreased levels of transforming growth factor beta receptor type 3 (TGFBR3), a protein with many functions including a role in heart morphogenesis. Single nucleotide polymorphisms of TGFBR3 have been found to be associated with gestational duration.…”
Section: Commentmentioning
confidence: 91%
“…The CVF proteome was analyzed in humans in various physiological conditions (1,2), mainly during pregnancy (3)(4)(5)(6)(7) or in several pathologies such as human papilloma virus (8) or candida albicans (9) infections. But few studies have investigated the CVF proteome during the cycle (10,11).…”
mentioning
confidence: 99%
“…Therefore, analysis of the CVF proteome can provide insights on the condition and functioning of the female reproductive system. Although many CVF proteomes have focused on pregnant women and aimed to discover biomarkers to predict preterm labor, the CVF proteome of healthy, nonpregnant women has received limited attention in comparison. Only three studies reported the CVF proteomes of healthy, nonpregnant women, which ranged in size from 59 to 685 proteins …”
Section: Introductionmentioning
confidence: 99%